Beyond economic and ecological standardisation - Tsing, Anna (The Australian journal of anthropology, 2009)
Supply chain capitalism forages among the ruins of military and industrial landscapes—and so do real foragers, such as Southeast Asian refugees picking wild mushrooms in the US Pacific Northwest for commercial shipment to Japan. This essay explores how supply chain dynamics thrive on deregulation and diversity, encouraging cultural and ecological variety as a source of profit. Supply chain values are created through diversity—and sometimes, disaster. I aim to provoke anthropologists to revive ethnography for the challenge of studying supply chains, as these erupt like mushrooms after a rain in the cracks of economic and ecological standardisation.